2014
DOI: 10.1007/s13203-014-0058-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lanthanum addition on the catalytic activity of γ-alumina supported bimetallic Co–Mo carbides for dry methane reforming

Abstract: The effect of lanthanum addition to c-alumina supported bimetallic carbides has been studied for the reaction of dry methane reforming using four different lanthanum loading levels of 1, 5, 10 and 15 wt% of lanthanum. It has been demonstrated that the addition of lanthanum to supported bimetallic carbides at low loading levels (1 wt%) results in smaller carbide crystallite sizes compared to catalysts containing either no lanthanum or higher lanthanum loading levels (5-15 wt%). Increased lanthanum loading resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Although noble metals display high activity and stability, their limited availability and high price have rendered them inappropriate for industrial use [13,14]. On the other hand, the first-row transition metals are cheaper and possess similar activity, but their stability is hampered by carbon deposition and particle sintering [15][16][17][18]. Therefore, development of Ni-based catalysts with high activity and resistance to deactivation due to carbon formation and metal sintering is essential for DRM.…”
Section: Introductionmentioning
confidence: 99%
“…Although noble metals display high activity and stability, their limited availability and high price have rendered them inappropriate for industrial use [13,14]. On the other hand, the first-row transition metals are cheaper and possess similar activity, but their stability is hampered by carbon deposition and particle sintering [15][16][17][18]. Therefore, development of Ni-based catalysts with high activity and resistance to deactivation due to carbon formation and metal sintering is essential for DRM.…”
Section: Introductionmentioning
confidence: 99%
“…formation was observed [18]. This suggests that a new composite has formed as a derivative from the carbon coking and sintering hence deactivating the active sites on Nickel.…”
Section: Co2 + Ch4 → 2co + 2h2-mentioning
confidence: 82%
“…They found that Ni−Mo 2 C synthesized by carburizing a coprecipitated (CP) precursor showed higher catalytic activity in the DRM reaction than a mechanically mixed (MM) precursor. During coprecipitation, Ni was incorporated into the NiMoO 4 matrix, avoiding metal 133,138,149 ZrO 2 , 139,140 MgO, 142 La 2 O 3 , 143 and several bimetallic oxides, 144 as described here.…”
Section: Strategies To Improve the Catalytic Performance Of Mo X C In...mentioning
confidence: 99%